Forensic approach to analyzing rape cases - Jakjovski, Zlatko; Jankova Ajanovska, Renata; Duma, Aleksej; Janeska, B.; Pavlovski, Goran; Marjanovic, D. (Elsevier BV, 2013)
With large number of criminal acts, such as rape and murder, identification of the perpetrator is very difficult to determine. The cause is the lack of sufficient quantity of biological traces provided as material evidence, or the biological material is decomposed and no result can be obtained by using other identification methods. Thus the case remains unsolved. The purpose of this research is to establish a reliable method for detecting semen presence in rape cases and to get DNA profile from the perpetrator of a crime. Vaginal swabs were taken using cotton swabs during gynecological examination or autopsy in 21cases. The chemical detection of semen presence was performed using Phospathesmo Kits. The DNA extraction was performed using QIAAamp1 DNA Mini Kit. The amplification was performed using AmpFistrIdentifilerKit and AmpFistrYfilerKit. The electrophoresis was performed using 310ABI squenator. Results indicate that DNA profile was obtained in 4caseswherechemical tests did not prove semen presence using Phospathesmo Kits. In one case, neither semen presence was chemically proven nor DNA profile was obtained for autosomal STRs, but a profile for Y-STRs was obtained. Our analyses indicate that when the victim’s body is examined with in the first few hours or the first day, a genetic profile of the perpetrator of the criminal act is obtained. Besides using autosomal STRs, we recommend Y-STRs to be used in all rape cases, too, thus separating the male from female profile, and also the male kinship relatedness in cases of incest could be followed, the rape performed by several blood-related men or similar.
Keywords: rape; DNA; Acid phospathase